Penyuluhan Alih Teknologi Pengolahan Produk Hortikultura dan Jamur Tiram di Nagari Padang Laweh, Sungai Pua, Kab. Agam - Ismed Ismed; Fauzan Azima; Novizar Nazir; Rini Rini; Daimon Syukri; Aisman Aisman; Purnama Dini Hari; Cesar Welya Refdi; Wellyalina Wellyalina; Felga Zulfia Radiana (Warta Pengabdian Andalas, 2020)
This community engagement activity has located a centre for horticultural agriculture, such as fruits and vegetables, in Nagari Padang Laweh, Sungai Pua district and Agam regency, West Sumatra Province. The focus products were tomato and oyster mushrooms at the time. Besides a farmer's land for tomatoes, there is also an oyster mushroom business managed by Hoki Jamur, producing 5-7 kg of fresh mushrooms per day. The problems faced by the partner's activity were a lack of processing technology for horticultural products. Tomatoes often through away when the price is low in the market. The production of oyster mushrooms is still fluctuating because cultivation is not good enough, and oyster has high water content, so it is easy to rot and have a short shelf life. Activities that have been carried out to solve partner problems were first evaluating horticulture and oyster mushroom cultivation activities at partner locations. Then, introducing processed post-harvest of horticulture to increase the selling value and its diversification to increase the shelf life of products by making tomato sauce and oyster mushroom meatballs. This activity went well and smoothly and was attended by local farmers, members of the Family Welfare Movement (PKK), and young entrepreneurs. Participants' enthusiasm for participating in this activity was high, especially during post-harvest product processing technology. This activity is expected to improve the quality and quantity of business production, income and economic welfare of partners and communities involved in partner business activities.